Web GIS solution and visualization towards sustainability of world heritage site / Abd. Manan Samad, Mat Salam Karnadi and Azman Mohd Suldi - Samad, Abd. Manan; Karnadi, Mat Salam; Mohd Suldi, Azman (Research Management Institute (RMI), 2013)
E-government is a promotion from the government side to encourage local authority using of new technologies for better operation. Web GIS is the one system which occupies e-government condition for geography information data sharing within organization and outside world. Sharing Information by using Web GIS by local authorities will probably improve performance inside organization to be more efficient, and could develop positive relationship with visitor and the public. Good Information presentation for spatial and non spatial information will facilitate relationship with public and also easy to produces decision for every development and planning which operates. This is easy system and can be increased internally and external inside each local council. Web based GIS is one of the systems who can used by local council in department of town planning for each local council to achieve objective inside of contents the agenda 21 produce in Earth Summit at Rio De Janeiro's conference in June 1992. Agenda 21 have produce are goals for Local Authority to implement negotiation process with society to formulate Local Agenda 21 respectively. So to deliver that meaning local authority must having equipment to channel information such as Geography’s information environmental area inside cater to societal involvement, private sector and powerful to cooperative the authorities inside planning and manage their environmental area direction to sustainable development. In the local council party for department of town planning it must have a Web based GIS system to channel information to civilians, private sector and local authority to be doing something planning result and development inside administration area by quick and accurate.